Hlengwe-Karanga conflict in Matibi 2 of Chiredzi district, 1950-2010 - Chisi, Taderera H. (Midlands State University Press, 2016)
The Hlengwe are dominant group in the southeast Lowveld of Zimbabwe since the 19th century. They were independently charting their course of socio-political and economic development till the turn of the 20th century when the whites began to have a direct interest in their area. The growing colonial interest in Hlengwe land between 1908 and the 1940s directly impacted on the hold of the Hlengwe on their land as they gradually lost it to the colonial master. By the end of the Second World War , they had lost most of their land and were driven into the reserves mainly Matibi 1 and 2, Sengwe and Sangwe. Matibi 2 was turned into an ethnic frontier after 1950 when the Karanga from the then Victoria province were driven into the area.